(untitled) (Research, Society and Development, 2021)
The health systems of the countries are suffering an increase in their expenses, for several reasons in Brazil, it is not different. From 2006 to 2013, investments in drug procurements by the Federal Government increased by 172%. Despite the achievements with the SUS, access to medicines is still not easy in several Brazilian regions. This work aims to analyze investments in medicines made by the Union, states and municipalities between 2010 and 2019 in order to identify regional differences in the application of these financial resources. It was observed that although the per capita investments in health were higher by the municipalities (R 926.54), when it comes to medicines, this per capita investment is higher by the Union (R 61.89). It was also identified that municipalities in the Northeast and North regions invest less in the procurement of medicines when compared to the national average (R 40.41), R 24.20 and R 23.58 respectively. When exploring the percentage of investment in medicine compared to the total investment in health among entities, it is possible to verify that states and municipalities have been decreasing their percentage of investment in medicines, highlighting the largest reduction made by the states (72.8% during the period analyzed). When the vulnerability indicator is used, it appears that the greater is the social vulnerability of the municipality, the lower are the amounts invested in medicines. The data show that the supply of medicines may be adversely affected in the main care entities (municipalities), especially in regions with a higher degree of social vulnerability. It is observed precisely where the support of the public health service is most dependent.